Investigation on the effect of varying bubble size and location in electrical resistance tomography using conducting boundary strategy - Suzanna, Ridzuan Aw; Farah Hanan, Azimi; Lia Safiyah, Syafie; Ruzairi, Abdul Rahim; Yasmin, Abdul Wahab; Nurain Izzati, Shuhaimi; Raja Siti Nur Adiimah, Raja Aris; Ida Laila, Ahmad (Springer, 2021)
This paper demonstrates a Linear Back Projection (LBP) algorithm based reconstruction of conductivity distributions to investigate the effect of varying different size and location of the bubble phantom in a vertical metallic column. Sixteen electrodes were placed evenly along the circumference of the column. Simulation and experimental studies applying conducting boundary strategy were conducted to investigate the performance of the system. The reconstructed images of the phantom under test are presented. All LBP images obtained by simulation and experiment then be presented and analysed using the Mean Structural Similarity Index (MSSIM) and Area Error (AE) analysis. The number and spatial distribution of the bubble phantom can be clearly distinguished wherever they are located in the pipeline. Bubbles with a greater size than 6 mm and especially the one that is located near the wall boundary are much easier to detect. This research has successfully been applied to a metallic column and contribute the knowledge on the effect of varying both the size and location of the bubble in the column.